2019
DOI: 10.1504/ijams.2019.10017148
|View full text |Cite
|
Sign up to set email alerts
|

Effects of buyer-supplier relationship on social performance improvement and innovation performance improvement

Abstract: Social performance improvement and innovation performance improvement is rapidly developing an area of research. Little empirical research has been conducted on the social performance outcomes in Pakistan and other developing countries. This research contributes to understanding how relational governance relates to social and innovation performance improvement in exporter and importer relationships. The analysis is based on cross-sectional base survey questionnaires on a sample of 239 senior managers from four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 48 publications
1
47
0
Order By: Relevance
“…Our results show that the indirect effect is positive and significant ( β = 0.046, SE = 0.020, p < 0.05, CI = 0.0158 to 0.0957, Table 5). The results confirm the results of Awan (2019), highlighting that knowledge sharing practices provide knowledge to firms about the task involved in the production process and social initiatives to develop new products, which in turn improves health and safety while reducing the risk of accidents. The results suggested that RAC can shape how firms with fewer resources come to develop and improve resources, which, in turn, may result in better improvement in employee health, improve employee satisfaction, and potentially affect the reduction in costs associated with the employee health and insurance.…”
Section: Resultssupporting
confidence: 83%
“…Our results show that the indirect effect is positive and significant ( β = 0.046, SE = 0.020, p < 0.05, CI = 0.0158 to 0.0957, Table 5). The results confirm the results of Awan (2019), highlighting that knowledge sharing practices provide knowledge to firms about the task involved in the production process and social initiatives to develop new products, which in turn improves health and safety while reducing the risk of accidents. The results suggested that RAC can shape how firms with fewer resources come to develop and improve resources, which, in turn, may result in better improvement in employee health, improve employee satisfaction, and potentially affect the reduction in costs associated with the employee health and insurance.…”
Section: Resultssupporting
confidence: 83%
“…Recently, Luzzini et al (2015) [44] found collaboration allowed firms to achieve resources that enable the firm to build on those resources and improve social performance. Conversely, Awan (2019) [45] found a positive relationship between joint planning and social performance improvements. [29] empirically showed that the adoption of interfirm collaboration on sustainability practices regarding social issues helped to improve social performance.…”
Section: Hypothesis (H1) Contract Governance Positively Affects a Fimentioning
confidence: 98%
“…In this sense, companies should pay special attention to their relationship with external stakeholders, which are part of their value chain, namely, suppliers, society, governments, creditors, investors, and customers. Relationship management is essential in supporting suppliers, resulting in improvements in social as well as innovation performance (Awan, 2019). Thus, to achieve sustainability in full, besides considering its strategic needs, the company must also be concerned with meeting current and future needs of its stakeholders (Dillick & Muff, 2015; Dillick & Hockerts, 2002).…”
Section: Literature Review: Sbscmentioning
confidence: 99%